Standardization of a dilution method for cyclosporin (C2) estimation in renal transplant patients - Kusumanjali, G. (Springer India, 2005)
Accurate monitoring of blood cyclosporin C2 levels is vital to prevent over immunosuppression and acute renal toxicity in patients who receive organ transplant. The matrix used to dilute patients’ C2 samples prior to the assay affected the final measured values. Hence there was a need to develop a method of dilution that would accurately estimate C2 levels when cyclosporin levels were beyond the calibration range of the method employed. Whole blood, cyclosporin free hemolysate and cell and protein free supernatant obtained after pretreatment of normal blood were used to dilute patients’ C2 samples. C2 was measured in 188 patients using the supernatant method of dilution. C2 was correlated with Co and dose of cyclosporin received by the patient. The use of cell and protein free supernatant obtained after pretreatment of normal blood as a C2 diluent detected higher levels of C2 in the sample. Measured C2 correlated significantly with Co and the cyclosporin dose received by the patient. The uniformly aqueous cell and protein free supernatant ensures uniform dilution of the patients’ C2 sample and measures higher cyclosporin levels.